Enzyme Encapsulation by Static Mixer Method for Hydrolysis of Lactose - Tan, Hui Ian; Hossain, Monwar; Zhang, Lu (International Journal of Biotechnology for Wellness Industries, 2012)
Enzyme immobilisation has been intensively investigated due to its advantages such as enzyme recovery, reusability and improved stability over a wide range of pH and temperatures. The encapsulation of β-galactosidase in κ-carrageenan is presented in this report for potential application in dairy industry. The immobilisation was carried out by emulsifying oil and κ-carrageenan with a static mixer device. This is a new approach and has the advantage of producing smaller beads (e.g. smaller than 100 µm size) which can be used in continuous processing. The main factors tested were the total flow rate through the static mixer (Qt, in the range 220 – 440 ml/min) and κ-carrageenan to oil volumetric fraction (ε, in the range 0.05-0.2). The average bead sizes obtained were in the range of 19 - 52 µm, with smaller sizes obtained with an increase of Qt. The bead sizes decreased with (i) the decrease in emulsified droplets coalescence and oil inclusion in the beads and (ii) with the decrease in the values of WGtop (defined by the weight percentage of beads found underneath the oil layer). The bead performance was tested using lactose and 2-nitrophenyl-β-galactopyranoside (ONPG) and the kinetic parameters, lactose conversion and stability were determined at the optimum conditions. The attained optimum pH and temperature were 7 (similar to free enzyme) and 21oC, respectively. The encapsulated β-galactosidase tested at optimum conditions in 5% (w/v) lactose solution was able to convert 76.47% of lactose after six days. These findings contribute to the further understanding of the encapsulation technique and demonstrates the potential of using κ-carrageenan as an encapsulation material for β-galactosidase.